On nanotribology modeling - Kravchuk, Alexandr Stepanovich (Computational Continuum Mechanics, 2008)
A new nanofriction model is proposed which is a generalization of the classical Tomlinson and Frenkel-Kontorova models. Generalization consists in taking into account the long-range force interaction in the frame of the theory of central pair interactions. Numerical solutions for friction forces as well as for force and displacement distributions in a deformed chain are constructed for all three models. The obtained solutions are compared, some important mechanical effects are revealed, and the applicability domain of the classical models is shown.